News interviews : a pragmalinguistic analysis - Jucker, Andreas H. (Pragmatics & beyond, 1986)
Jucker endeavors to test pragmatic concepts (such as Grice's principles of conversational inference) by applying them to concrete data. This application leads to suggestions for various modifications in the available pragmatic methodology. While pursuing this theoretical goal, he makes a significant contribution to descriptive pragmatics by offering a detailed picture of linguistically relevant aspects of news interviews, which show communicative behavior in 'laboratory conditions' where as many influencing factors as possible are kept stable while the influence of one specific factor at a tim.